Study of Renal Function Test in Pregnant Women with Pre-eclampsia: A Hospital Based Cross-Sectional Study - Sah, Bishesh; Rawat, Durga BC; Karn, Subhash Lal; Sah, Bishal; Sapkota, Suraksha; Mishra, Akash; Malla, Pragya (Journal of Nepalgunj Medical College, 2025)
Introduction: The multifactorial disease known as preeclampsia presents significant hazards throughout pregnancy and often results in renal impairment.Aims: To evaluate renal function tests in pregnant women with preeclampsia compared to normotensive pregnant women.Methods: A Hospital based comparative cross-sectional study was carried out for a period of six months from December 2024 to June 2025, involving 80 participants (40 with Pre-eclamptic pregnant women and 40 normotensive pregnant women) aged 18 to 45 years at gestational ages after 30 weeks. Serum urea, creatinine, and uric acid levels were estimated, and statistical analysis was performed using SPSS version 25. Results: The median age was 27.5 years and 25 years in the pre-eclamptic and normotensive group respectively. The pre-eclamptic group manifested significant increases in serum urea (21.7 mg/dl vs. 15.8 mg/dl, p < 0.001), creatinine (0.70 mg/dl vs. 0.62 mg/dl, p = 0.039), and uric acid (7.08 mg/dl vs. 5.5 mg/dl, p < 0.001) compared to normotensive group. The pre-eclamptic group systolic and diastolic blood pressure readings were 150.0 mmHg and 100.0 mmHg respectively which vary significantly compared to the normotensive group measurements which were 110.0 mmHg and 70.0 mmHg.Conclusion: Our study found that preeclampsia had a negative impact on renal function, as evidenced by elevated levels of serum urea, creatinine and uric acid. These results highlight the importance of monitoring renal function in pregnant women with hypertension since these measurements are crucial indicators of renal impairment in pre-eclampsia.